Understanding Digital Signature through a Conceptual Approach to Improve Efficiency, Access, and Quality of Fintech - Rasmuddin Rasmuddin; Wahyudi Umar; Sudirman Sudirman (Faculty of Law, Universitas Pekalongan, 2023)
This study aims to deepen the understanding of the concept of digital signature in the context of the fintech industry, focusing on efforts to improve the efficiency, accessibility, and quality of fintech services. Digital signatures are a key component in modern fintech transactions and services, which are important in securing information and maintaining data integrity in a digital environment. This research method involves a conceptual approach consisting of literature analysis, case studies, and an in-depth understanding of digital signature technology and its impact on the fintech ecosystem. Basic concepts such as cryptography, algorithms, and digital security principles will be carefully examined to understand the foundations of digital signature technology. In addition, this research will also explore the latest developments in the use of digital signatures in the fintech industry, as well as their impact on operational efficiency, service accessibility, and transaction quality. The results of this research are expected to provide in-depth insights into the role of digital signatures in changing the fintech landscape. By understanding this concept better, stakeholders in the fintech industry can optimize the use of digital signatures to improve their speed, security, and quality of service. This is expected to help create a more efficient, accessible, and reliable fintech environment for consumers and businesses. This research can also be the basis for further research in the field of fintech security and related technological innovations.